ASME 2006 Internal Combustion Engine Division Spring Technical Conference (ICES2006) 2006
DOI: 10.1115/ices2006-1317
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Simulation Code for Hydrogen Fuelled SI Engines

Abstract: Hydrogen is an attractive alternative energy carrier, which could make harmful emissions, global warming and the insecurity concerning oil supply a thing of the past. Hydrogen internal combustion engines can be introduced relatively easily, from a technological as well as from an economic point of view. This paper discusses the development of a model for the combustion of hydrogen in spark ignition engines, which has lead to a simulation program that can assist the optimization of these engines. The importance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Alternative fuels, like ethanol, natural gas, propane, and acetylene, are substituting for fossil fuels. There are many experimental works on the functioning of automobiles with these alternative fuels, and therefore, few publications are made to compare effects of these fuels together. The majority of previous literature show a comparison between two or three fuels . In comparison of a hydrogen/gasoline engine, Verhelst et al concluded that the BTE of a hydrogen engine surpasses than that of a gasoline engine.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Alternative fuels, like ethanol, natural gas, propane, and acetylene, are substituting for fossil fuels. There are many experimental works on the functioning of automobiles with these alternative fuels, and therefore, few publications are made to compare effects of these fuels together. The majority of previous literature show a comparison between two or three fuels . In comparison of a hydrogen/gasoline engine, Verhelst et al concluded that the BTE of a hydrogen engine surpasses than that of a gasoline engine.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Laminar burning velocities are compiled into a correlation that may be used as an input for turbulent combustion models employing an analytical expression adopted from Verhelst 20 in the form of…”
Section: Computational Modelmentioning
confidence: 99%
“…With respect to the wide range of equivalence ratios present in hydrogen DI engines, an experimental laminar flame speed correlation presented by Verhelst 20 is extended to the rich regime. The original correlation reproduces measurements of the ‘Leeds’ combustion bomb covering fuel-to-air equivalence ratios of ϕ ≤ 1 (λ ≥ 1).…”
Section: Computational Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…In Verhelst's literature [7] quasi-dimensional model was preferred to multi-dimensional one because of a reasonable accuracy and fast computation on PC system. And they developed a complete cycle simulation code for SI engine and they looked thoroughly at the turbulent combustion in hydrogen fuelled engine.…”
Section: Introductionmentioning
confidence: 99%